2021
DOI: 10.1111/xen.12667
|View full text |Cite
|
Sign up to set email alerts
|

The effects of necrostatin‐1 on the in vitro development and function of young porcine islets over 14‐day prolonged tissue culture

Abstract: Background Necrostatin‐1 (Nec‐1) supplementation to tissue culture media on day 3 has recently been shown to augment the insulin content, endocrine cellular composition, and insulin release of pre‐weaned porcine islets (PPIs); however, its effects were only examined for the first 7 days of tissue culture. The present study examined whether the addition of Nec‐1 on day 3 could further enhance the in vitro development and function of PPIs after 14 days of tissue culture. Methods PPIs were isolated from 8‐ to 15‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To further test the efficacy of nec‐1 in prolonged exposure to see the effect on neonatal and adult porcine islet cell composition, they tested this over an extended 14‐day culture period and undertook flow cytometric analysis of the preps at two time points. They focused their analysis of the cells at 7 and 14 days culture points and demonstrated that enhanced attributes previously seen in the cell culture does not continue to significantly increase past day 7, and proliferation, islet recovery, and GLUT2 expression significantly decreases between day 7 and 14; however, the use of nec‐1 in culture did continue to have an enhanced effect on endocrine composition but was not significantly different between day 7 and 14 where the alpha and delta cells continued to increase 15 …”
Section: Improving Function Of Porcine Islet Cells For Treatment Of Type 1 Diabetesmentioning
confidence: 96%
See 1 more Smart Citation
“…To further test the efficacy of nec‐1 in prolonged exposure to see the effect on neonatal and adult porcine islet cell composition, they tested this over an extended 14‐day culture period and undertook flow cytometric analysis of the preps at two time points. They focused their analysis of the cells at 7 and 14 days culture points and demonstrated that enhanced attributes previously seen in the cell culture does not continue to significantly increase past day 7, and proliferation, islet recovery, and GLUT2 expression significantly decreases between day 7 and 14; however, the use of nec‐1 in culture did continue to have an enhanced effect on endocrine composition but was not significantly different between day 7 and 14 where the alpha and delta cells continued to increase 15 …”
Section: Improving Function Of Porcine Islet Cells For Treatment Of Type 1 Diabetesmentioning
confidence: 96%
“…The media in which the cells are cultured is of significant importance indicating that additives during cell culture not only benefit cell proliferation during the culture phase by reducing the fragility from mechanical stress during the isolation process, 14 as demonstrated by Lau et al. with hypoxia‐related cell death, 15 but also inhibiting apoptosis and increasing revascularization of the cells following transplantation 16,17 …”
Section: Improving Function Of Porcine Islet Cells For Treatment Of Type 1 Diabetesmentioning
confidence: 99%
“… Jo et al (2015) also found that Necrostatin-1 improves the survival of mouse oocytes. Numerous studies show that Necrostatin-1 promotes the maturation, development, and graft function of neonatal porcine islets ( Lau et al, 2020a , b , 2021 ), providing an effective strategy for the future application of islet grafts ( Qin et al, 2022 ). Emerging evidence suggests that Necrostatin-1 has potential radical scavenging activities ( Ushijima and Monzaki, 2023 ).…”
Section: Application Of Necrostatin-1mentioning
confidence: 99%
“…Previously, we determined that culturing pre-weaned porcine islets (PPIs) in media supplemented with Nec-1 immediately after islet isolation for 7 days significantly augmented islet insulin content, proportion of endocrine cells, and in vitro insulin secretion [15]. Our recent studies have further shown that 100 µM of Nec-1 was the most effective dose to enhance the in vitro maturation of PPIs for up to 7 days during tissue culture [16,17]. However, these investigations lack a detailed comparison of the optimal timing to supplement Nec-1 to islet tissue culture and its impact on the in vivo function of PPIs.…”
Section: Introductionmentioning
confidence: 99%